Association Between Substance Use and Professional Outcomes Among Medical Students: Findings from a Canadian Cross-sectional Survey. Issue 4 (1st December 2022) - Bahji, Anees; Danilewitz, Marlon; Maser, Brandon; Guerin, Eva; Frank, Erica
ABSTRACT: Background: While substance use is common among medical students, there is limited research on this topic involving Canadian medical students or exploring its associations with professional outcomes. The present study examines the association between Canadian medical students' substance use and related counselling attitudes and practices, career satisfaction, academic/clinical workload, and the medical school environment. Methods: We sent an electronic cross-sectional survey to students attending all 17 Canadian medical schools between November 2015 and March 2016. A total of 4438 participants completed the survey across 4 years of study, with a participation rate of 40.2%. We considered 4 categories of substance use: cannabis, alcohol, nonmedical use of prescription stimulants (NPS), and cigarettes. Covariates included professional attitudes (eg, career satisfaction, distress, patient counselling on alcohol or smoking cessation), specialty of interest, learner mistreatment, and perceived medical school support. We used multivariate logistic regression models, generating adjusted odds ratios (AORs), to examine covariates associated with substance use and how substance use (as a covariate) was associated with different professional outcomes. Results: Individuals more interested in "lifestyle" specialties (AOR, 1.81; 95% CI, 1.08–3.05) and surgical specialties (AOR, 1.69; 95% CI, 1.16–2.47) were more likely to report excessive alcohol use. Those interested in primary care were more likely to report cannabis use in the past 12 months (AOR, 1.85; 95% CI, 1.14–3.00). We did not identify significant associations between specialty of interest and current cigarette or NPS use in the past 12 months. However, excessive alcohol use was associated with greater career satisfaction (AOR, 1.24; 95% CI: 1.04–1.49), whereas NPS in the past 12 months was associated with poorer career satisfaction (AOR, 0.63; 95% CI: 0.42–0.93). In addition, there was a negative association between NPS use and the ability to handle workloads due to physical (AOR, 0.31; 95% CI, 0.18–0.54) or mental health issues (AOR, 0.46; 95% CI, 0.30–0.71), but not for other substances. We also found significant negative associations between current cigarette use and the perceived relevance of smoking cessation counselling (AOR, 0.48; 95% CI: 0.29–0.80) and alcohol cessation counselling (AOR, 0.42; 95% CI: 0.25–0.70). Conclusions: These findings suggest that specific patterns of substance use in medical students appeared to be significantly associated with some professional outcomes, specialty of interest, and attitudes towards addiction-related clinical practice. Encouraging medical students to practise healthy habits, including minimizing harmful substance use behaviours, could be an important target for improving medical students' health and their patient care. Abstract : Contexte: Bien que la consommation d'alcool et de drogues soit courante chez les étudiants en médecine, peu d'études sur ce sujet ont été menées auprès d'étudiants canadiens en médecine ou ont exploré ses liens avec les résultats professionnels. La présente étude examine l'association entre la consommation de substances psychoactives des étudiants canadiens en médecine et les comportements et habitudes en matière de suivi psychologique, la satisfaction à l'égard de la carrière, la charge de travail universitaire/en clinique et l'environnement de la faculté de médecine. Méthodes: Nous avons fait parvenir une enquête transversale électronique aux étudiants fréquentant les 17 facultés de médecine canadiennes entre novembre 2015 et mars 2016. Au total, 4 438 participants ont répondu à l'enquête sur quatre années d'études, avec un taux de participation de 40, 2 %. Nous avons considéré quatre catégories de consommation de substances : le cannabis, l'alcool, l'utilisation non médicale de stimulants sur ordonnance (NSO) et les cigarettes. Les covariables comprenaient les attitudes professionnelles (par exemple, la satisfaction professionnelle, la détresse, les conseils aux patients sur l'arrêt de l'alcool ou du tabac), la spécialité choisie, les maltraitances infligées aux étudiants et le soutien perçu de la faculté de médecine. Nous avons utilisé des modèles de régression logistique multivariés, générant des rapports de cotes ajustés (RCA), pour examiner les covariables associées à la consommation de substances et la façon dont la consommation de substances (en tant que covariable) était associée à différents résultats professionnels. Résultats: Les personnes plus intéressées par les spécialités "mode de vie" (RCA, 1, 81 ; IC 95 %, 1, 08-3, 05) et les spécialités chirurgicales (RCA, 1, 69 ; IC 95 %, 1, 16-2, 47) étaient plus susceptibles de déclarer une consommation excessive d'alcool. Les personnes intéressées par les soins primaires étaient plus susceptibles de déclarer avoir consommé du cannabis au cours des 12 derniers mois (RCA, 1, 85 ; IC à 95 %, 1, 14-3, 00). Nous n'avons pas identifié d'associations significatives entre la spécialité choisie et la consommation de cigarettes ou de NSO au cours des 12 derniers mois. Toutefois, la consommation excessive d'alcool était associée à une plus grande satisfaction professionnelle (RCA, 1, 24 ; IC à 95 % : 1, 04-1, 49), tandis que la consommation de NSO au cours des 12 derniers mois était associé à une plus faible satisfaction professionnelle (RCA, 0, 63 ; IC à 95 % : 0, 42-0, 93). En outre, il existe une association négative entre la consommation de NSO et la capacité à gérer la charge de travail en raison de problèmes de santé physique (RCA, 0, 31 ; IC à 95%, 0, 18-0, 54) ou mentale (RCA, 0, 46 ; IC à 95%, 0, 30-0, 71), mais pas pour les autres substances. Nous avons également constaté des associations négatives significatives entre l'usage de la cigarette et la pertinence perçue des conseils en matière d'arrêt du tabac (RCA, 0, 48 ; IC 95 % : 0, 29-0, 80) et des conseils en matière d'arrêt de l'alcool (RCA, 0, 42 ; IC 95 % : 0, 25-0, 70). Conclusion: Ces résultats suggèrent que des modèles spécifiques de consommation de substances psychoactives chez les étudiants en médecine semblent être significativement associés à certains résultats professionnels, à la spécialité choisie et aux attitudes envers la pratique clinique liée à la dépendance. Encourager les étudiants en médecine à adopter des habitudes saines, notamment en minimisant les comportements nocifs liés à la consommation de substances, pourrait être un objectif important pour améliorer la santé des étudiants en médecine et les soins aux patients.